2021
DOI: 10.4102/sajhrm.v19i0.1513
|View full text |Cite
|
Sign up to set email alerts
|

The impact of talent management on job satisfaction of registered nurses in Malawian public hospitals

Abstract: Orientation: Job satisfaction is the paramount tool to gauge whether employees are willing to stay or leave an organisation. Talent management as a key aspect of human resources management has a fundamental role to play in ensuring that employees are satisfied with their work so that they can stay within the organisation.Research purpose: The purpose of this study was to establish the impact of talent management on job satisfaction of registered nurses in public hospitals of Malawi.Motivation for study: There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…Additionally, Othman, Khalil, (2018) (30) revealed that talent management reduces demotivation, but does not significantly influence the creativity of architectural firms. While, inconsistent with, Dzimbiri, Molefi, (2021) (31) conducted a crosssectional survey on 834 registered nurses and the findings of the study demonstrate that talent management practices do not contribute towards job satisfaction of registered nurses in Malawian public hospitals. Similarly, Mensah, Bawole, (2017) (32) suggested that talent management does not only have a direct effect, but also an indirect effect on talented employees' affective commitment and decreased quit intentions via person-job fit working in selected parastatal institutions in Ghana.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, Othman, Khalil, (2018) (30) revealed that talent management reduces demotivation, but does not significantly influence the creativity of architectural firms. While, inconsistent with, Dzimbiri, Molefi, (2021) (31) conducted a crosssectional survey on 834 registered nurses and the findings of the study demonstrate that talent management practices do not contribute towards job satisfaction of registered nurses in Malawian public hospitals. Similarly, Mensah, Bawole, (2017) (32) suggested that talent management does not only have a direct effect, but also an indirect effect on talented employees' affective commitment and decreased quit intentions via person-job fit working in selected parastatal institutions in Ghana.…”
Section: Discussionmentioning
confidence: 84%
“…The main objective of every organisational strategy is to achieve the effectiveness and efficiency of the operation, which could lead the organisation to its mission (Dzimbiri & Molefi, 2021). In culture, people and organisational approach, TM is one of the pivotal aspects that mainly focuses on how digital transformation views TM and what actions should be undertaken to cover strategy planning, workforce planning, talent acquisition, talent development, digital learning and employee engagement to improve organisational performance.…”
Section: Digitalisation and Digital Transformationmentioning
confidence: 99%
“…The results of the study state that talent management has an influence on employee job satisfaction, the more the company has good talent and can maintain it, the employees will feel satisfied. (Dzimbiri & Molefi, 2021;Sariwulan et al, 2021) Knowledge management is an activity that has been widely applied in companies. (Mladenović & Krajina, 2020;Zhang et al, 2020).…”
Section: Talentmentioning
confidence: 99%
“…Many studies that discuss talent management, knowledge management, job satisfaction and employee performance as conducted by (Saleh & Atan, 2021;Banuari et al, 2021;Ratnawati & Subudi, 2018;Dzimbiri & Molefi, 2021;Manfredi Latilla et al, 2018) but unfortunately the study did not explain specifically about all the variables so that the researchers tried to fill the gaps in previous research. Job satisfaction will be studied as a mediator in improving employee performance through talent and knowledge management in this study.…”
Section: Talentmentioning
confidence: 99%
See 1 more Smart Citation